Kontribusi Al-Khalil Bin Ahmad Al-Farahidi dalam Ilmu-Ilmu Bahasa Arab - Damhuri Dj Noor; Muhtar Miolo (LP2M IAIN Sultan Amai Gorontalo, 2019)
This article seeks to explain the development of Arabic linguistics in the hands of al-Khalil bin Ahmad al-Farahidi. Although not the first pioneers of the science of Nahwu and Sharf, he was seen as the layer of the formal rules of Nahwu and Sharf. His contribution in the Nahwu and sharf field includes, codified all linguistic cases that had been carried out by the predecessor. He then perfected the analogous rules, formulated technical terms Nahwu and Sharf, formulated morphological rules, and created punctuation in Arabic. In addition to having expertise in the field of linguistics, he also has extensive knowledge in the sciences of Sharia and Mathematics. More than that, he has an extraordinary talent in the field of Music Arts and stringing. His intelligence in the last two areas helped him in creating the principles of the science of al-udarudh and al-qawafi.